Especiação química de arsênio inorgânico no estuário da Laguna dos Patos (RS, Brasil) - Farias,Josiane dos Santos (2012)
This study optimized and validated a method to perform chemical speciation of inorganic arsenic in water samples collected under the Monitoring Program of the Port of Rio Grande-RS in July and October 2010 from the Laguna dos Patos Estuary (RS, Brazil). The flow injection hydride generation atomic absorption spectrometry technique was employed, allowing quantification of As3+ and As5+ present in estuarine water samples. Data interpretation for results generated using the improved method for analyzing water samples collected from Laguna dos Patos Estuary was done by main components analysis.